Prognostic value of resting cardiac power index depends on mean arterial pressure in dilated cardiomyopathy - Ryota Morimoto (ESC Heart Failure, 2021)
Abstract Aims In recent decades, haemodynamic parameters have been estimated for risk stratification and determining treatment strategies for patients with non‐ischaemic dilated cardiomyopathy (DCM). In various invasive procedures, the cardiac pumping capability is defined as cardiac power output (CPO), which is calculated by multiplying cardiac output by the mean arterial pressure. Lower CPO values in advanced heart failure predict adverse outcomes. However, few studies discuss the prognostic value of CPO in mild‐to‐moderate phase patients. This study aimed to determine the value of the cardiac power index (CPI) obtained from the resting CPO for predicting the prognosis of patients with New York Heart Association Functional Class II or III DCM. Methods and results From March 2000 to January 2020, a total of 623 cardiomyopathy patients were evaluated for haemodynamic parameters. Patients with secondary cardiomyopathy, ischaemic cardiomyopathy, valvular heart disease, and Class IV cardiomyopathy were excluded. A total of 176 DCM patients fulfilled the criteria for inclusion. Patients were 51.7 ± 12.5 years old (mean ± standard deviation) with a mean left ventricular ejection fraction of 32.1 ± 9.2%. The patients were divided into two groups by their median CPI (CPI < 0.52, low‐CPI; CPI ≥ 0.52, high‐CPI). No significant differences were found in the left ventricular end‐diastolic diameter, left ventricular ejection fraction, or pulmonary arterial wedge pressure between the groups. The probability of cardiac event‐free survival was significantly lower for low‐CPI than for high‐CPI groups by Kaplan–Meier analysis (P = 0.012), even with no significant difference between the high and low cardiac index groups (P = 0.069). Furthermore, Cox proportional hazards regression analysis revealed that, in addition to the CPI, the systolic and mean arterial pressure involved in CPI calculation were independent predictors of cardiac events. Indeed, among these factors, mean arterial pressure had the strongest prognostic ability. Conclusions Although CPI is effective for stratifying DCM and predicting cardiac events in patients with Class II/III DCM, this prognostic value depends on mean arterial pressure.